Pengaruh Pemberian Jus Buah Bit dengan Kenaikan HB Remaja Putri di SMK Guna Dharma Kota Bandar Lampung - Agustina, Sera; Susilawati, Susilawati; Anggraini, Anggraini; Yantina, Yuli (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT English translation. Iron nutrition anemia can cause a decrease in physical ability, work productivity, and thinking ability. SMK GUNA DHARMA Bandar Lampung City found the highest population of adolescent girls with anemia as many as 92 adolescent girls and 30 adolescent girls of whom had anemia (31.5%) based on the results of laboratory checks and characteristics during physical examination. In addition, based on the results of interviews, young women said they never took drugs or foods that could help increase blood regularly. The purpose of this study is to determine the effect of giving beet juice with an increase in Hb for young women at SMK Guna Dharma Bandar Lampung City in 2023. Type of quantitative research. Pre-experimental research design with one group pretest – posttest design approach. The population of grade 1 and 2 girls at SMK Guna Dharma Bandar Lampung City with a total of 92 people in 2023. Purposive sampling technique. Data analysis using univariate and bivariate using Wilcoxon test.  An influence of giving beet juice with an increase in Hb for young women at SMK Guna Dharma Bandar Lampung City in 2023.The average Hb in adolescent girls before being given beetroot juice with a Mean of 10.470gr / dl which means adolescent girls have mild anemia. The average Hb in adolescent girls after being given beetroot juice with a mean of 11.117gr / dl which means adolescent girls are no longer anemic / normal. The results of the statistical test obtained a mean difference test of 1.06 P-value = 0.000 (<0.05) which means that there is an influence of giving beet juice with an increase in Hb for young women at SMK Guna Dharma Bandar Lampung City in 2023. English translation. it is expected for young women to always consume beet juice, and consumption of foods that contain lots of iron is highly recommended in adolescents who have anemia, because it will help the process of increasing Hb. Keywords:English translation.  Beetroot Juice, HB Rise, Young WomenEnglish translation.